2015
DOI: 10.1242/dmm.020172
|View full text |Cite
|
Sign up to set email alerts
|

Precision-cut kidney slices (PCKS) to study development of renal fibrosis and efficacy of drug targeting ex vivo

Abstract: Renal fibrosis is a serious clinical problem resulting in the greatest need for renal replacement therapy. No adequate preventive or curative therapy is available that could be clinically used to target renal fibrosis specifically. The search for new efficacious treatment strategies is therefore warranted. Although in vitro models using homogeneous cell populations have contributed to the understanding of the pathogenetic mechanisms involved in renal fibrosis, these models poorly mimic the complex in vivo mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…However, both untransfected and transfected PCKS contained some apoptotic proximal tubules (marked by loss of nuclei and swelling of cells), although the general morphology remained unaffected. Apoptosis in proximal tubules has been reported previously, and the authors suggested it is caused by a disturbed pre-urine flow [8,22]. As such, observed morphological changes in PCKS are not attributable to the siRNA.…”
Section: Slice Viabilitymentioning
confidence: 66%
See 1 more Smart Citation
“…However, both untransfected and transfected PCKS contained some apoptotic proximal tubules (marked by loss of nuclei and swelling of cells), although the general morphology remained unaffected. Apoptosis in proximal tubules has been reported previously, and the authors suggested it is caused by a disturbed pre-urine flow [8,22]. As such, observed morphological changes in PCKS are not attributable to the siRNA.…”
Section: Slice Viabilitymentioning
confidence: 66%
“…Furthermore, the greater number of cells per unit volume in PCKS might have also affected the penetration of Accell siRNA by restraining the diffusion of siRNA from a region of high concentration to a region of low concentration. Researchers have previously shown that fluorescent lysozyme (~15 kDa) diffused into PCKS prepared from mice [21,22]. As such, it is not surprising that Accell siRNA, which has a comparable molecular weight to the fluorescent lysozyme, could also diffuse into PCKS.…”
Section: Slice Transfectionmentioning
confidence: 99%
“…The PCKS model was constructed according to Potti et al's protocol [3]. Male C57BL/6 mice (weight: 25-30 g) were purchased from Beijing Vital River Laboratories (Beijing, China).…”
Section: Construction Of the Pcks Modelmentioning
confidence: 99%
“…Although in vitro cell culture models have bettered our understanding of renal fibrosis [2], these models cannot adequately mimic the in vivo environment [3]. To address the limitation, a recent 2015 study by Poosti et al constructed an ex vivo precision-cut kidney slice (PCKS) model with the aim of mimicking renal fibrosis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation